Practice patterns in venous thromboembolism (VTE) prophylaxis in thoracic surgery: a comprehensive Canadian Delphi survey - Agzarian, John; Linkins, Lori-Ann; Schneider, Laura; Hanna, Waël C.; Finley, Christian J.; Schieman, Colin; Perrot, Marc De; Crowther, Mark; Douketis, James; Shargall, Yaron (Journal of Thoracic Disease, 2017)
Background: The incidence of venous thromboembolic events (VTE) after resection of thoracic malignancies can reach 15%, but prophylaxis guidelines are yet to be established. We aimed to survey Canadian practitioners regarding perioperative risk factors for VTE, impact of those factors on extended prophylaxis selection, type of preferred prophylaxis, and timing of initiation and duration of thromboprophylaxis. Methods: A modified Delphi survey was undertaken over three rounds with thoracic surgeons, thoracic anesthesiologists and thrombosis experts across Canada. Participants were asked to rate each parameter on a ten-point scale. Agreement was determined a priori as an item reaching a coefficient of variation of ≤30% (0.3), with the item then discontinued from later rounds. Results: In total, 72, 57 and 50 respondents participated in three consecutive rounds, respectively. Consensus was reached on previous VTE, age, cancer diagnosis, thrombophilia, poor mobilization, extended resections, and pre-operative chemotherapy as risk factors. Consensus on risk factors impacting extended prophylaxis decisions was achieved on cancer diagnosis, obesity, previous VTE and poor mobilization. With respect to perioperative prophylaxis, once daily low-molecular-weight heparin (LMWH) was the only parameter that demonstrated agreement as a common practice pattern. No agreement was achieved regarding the role of mechanical prophylaxis, unfractionated heparin (UFH) or timing of initiation of peri-operative treatment. VTE prophylaxis until discharge reached agreement but there was substantial variability regarding the role of extended prophylaxis. Conclusions: There is agreement between Canadian clinicians treating patients with thoracic malignancies regarding most risk factors for VTE, but there is no agreement on timing of initiation of prophylaxis, the agents used or factors mandating usage of extended prophylaxis.